Substantiation of the use of virtual and augmented reality as a means of developing cognitive interest in children - Loseva-Rimsha, Nataliia Sergeevna (Современное образование, 2022)
The article discusses the options for using virtual and augmented reality in education, provides a justification for their use for the development of interest in children and motivation. VR and AR tools will soon become full-fledged educational tools, as the presentation of information is interesting and understandable. And the coronavirus epidemic has attracted the attention of people forced to stay at home to online education and interactive tools that can make learning more visual. Online classes can be a great way to involve the student even more in the educational process through immersion and detail. The novelty of the research is that it was possible to justify the need for the use of virtual reality in the educational process using psychological and astrological tools. By combining astrological studies obtained by mathematical calculations with psychological knowledge, it makes it possible to build a teacher's work in the right and unique direction. Therefore, each educational product with augmented reality can be made as individual as possible by dividing children into four main groups using astrological calculations. Someone is receptive and learns more successfully with a dynamic presentation, someone from a colorful one, and there are children who perceive more chrome and static.